Nebkhas play important roles in desertification control and biodiversity protection in arid and semi-arid regions of China - Weicheng Luo (Taylor & Francis Group, 2020)
Nebkhas are isolated mounds vegetated with burial-tolerant desert plants that trap windborne sediment within their canopies. Nebkhas are critical to desertification control and biodiversity protection of oases in arid and semi-arid regions of China, as they (ⅰ) trap windborne sediments and ensure oasis security; (ⅱ) as “fertile islands,” nebkhas can trap and provide a suitable micro-environment for seeds, birds, and small soil animals, and increase biodiversity; (ⅲ) increase the soil surface roughness and significantly reduce soil erosion following heavy rain. However, the establishment of sand-fixing vegetation and over-grazing significantly limits the development and accelerate the degradation of nebkhas, threatening oasis ecosystems. We provide background and recommendations for protective measures for nebkha landscapes in arid and semi-arid areas of China to aid managers in oasis protection.